1993
DOI: 10.1016/0968-4328(93)90070-h
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of multinucleate giant cells

Abstract: A survey of the available ultrastructural data on physiologically and pathologically occurring and virally-induced multinucleate giant cells (MNGCs) is presented. Emphasis is initially placed upon the bone osteoclast, the skeletal muscle myotube and the placental syncytiotrophoblast. The widespread occurrence of MNGCs in a range of pathological situations is discussed, with emphasis upon the broad involvement of the macrophage in inflammatory responses. Many viruses produce cell fusion in vivo and in vitro whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 105 publications
1
5
0
Order By: Relevance
“…4a). The medium used for low-temperature embedding does not visualize vesicular structures well enough to enable their identification, but as a whole our observations are in line with reports by Grief et al (1991) and others (reviewed in Harris, 1993), which showed that the major producers of the virus were multinuclear cells, while single cells were mostly free of signs of assembly or budding. No immunolabeling for Gag was done in the above papers, limiting our ability to make direct comparisons.…”
Section: Specific Situation In Multinuclear Cellssupporting
confidence: 90%
“…4a). The medium used for low-temperature embedding does not visualize vesicular structures well enough to enable their identification, but as a whole our observations are in line with reports by Grief et al (1991) and others (reviewed in Harris, 1993), which showed that the major producers of the virus were multinuclear cells, while single cells were mostly free of signs of assembly or budding. No immunolabeling for Gag was done in the above papers, limiting our ability to make direct comparisons.…”
Section: Specific Situation In Multinuclear Cellssupporting
confidence: 90%
“…Throughout the 1970s, C-type retrovirus(es) were detected by EM in the normal placenta of baboons and a number of other primates, cats, mice, and guinea pigs 6 (see Daniel and Chilton 10 for review), as well as in humans. 11,12 These data were supported by the isolation of retroviral particles from the baboon and rhesus monkey.…”
Section: Detection and Isolation Of Animal And Human Placental Ervmentioning
confidence: 99%
“…The role of apoptosis, if any, in the ultimate degeneration of placental tissue remains to be firmly established. Ultrastructural indications from the formation of clustered nuclei containing condensed chromatin (nuclear/syncytial knots) in human placental syncytiotrophoblast at term 6,72 (even more dramatically under conditions of rhesus incompatibility), is characteristic of apoptosis. The claim that apoptosis can be identified in human trophoblastic cells by in situ nick end labeling of fragmented DNA 73 provides evidence that controlled cell death does play a role in the terminal differentiation of the placenta.…”
Section: Placental Development Structure and Life Spanmentioning
confidence: 99%
See 2 more Smart Citations